GG attenuates tenofovir disoproxil fumarate-induced bone loss in male mice gut-microbiota-dependent anti-inflammation - Hao Liu; Ranli Gu; Wei Li; Wen Zhou; Zhe Cong; Jing Xue; Yunsong Liu; Qiang Wei; Yongsheng Zhou (SAGE Publishing, 2019)
Background: Although antiretroviral agents trigger bone loss in human immunodeficiency virus patients, tenofovir disoproxil fumarate (TDF) induces more severe bone damage, such as osteoporosis. While, the mechanisms are unclear, probiotic supplements may be effective against osteoporosis. Methods: C57BL6/J mice were administered with Lactobacillus rhamnosus GG (LGG)+TDF, TDF, and zoledronic acid+TDF, respectively. Bone morphometry and biomechanics were evaluated using microcomputed tomography, bone slicing, and flexural tests. The lymphocyte, proinflammatory cytokines, and intestinal permeability levels were detected using enzyme-linked immunosorbent assays, quantitative real-time polymerase chain reaction, and flow cytometry. The gut microbiota composition and metabolomics were analyzed using 16S recombinant deoxyribonucleic acid pyrosequencing and ultra-performance liquid-chromatography-quadrupole time-of-flight mass spectrometry. Results: LGG administered orally induced marked increases in trabecular bone microarchitecture, cortical bone volume, and biomechanical properties in the LGG+TDF group compared with that in the TDF-only group. Moreover, LGG treatment increased intestinal barrier integrity, expanded regulatory T cells, decreased Th17 cells, and downregulated osteoclastogenesis-related cytokines in the bone marrow, spleen, and gut. Furthermore, LGG reconstructed the gut microbiota and changed the metabolite composition, especially lysophosphatidylcholine levels. However, the amount of N-acetyl-leukotriene E4 was the highest in the TDF-only group. Conclusion: LGG reconstructed the community structure of the gut microbiota, promoted the expression of lysophosphatidylcholines, and improved intestinal integrity to suppress the TDF-induced inflammatory response, which resulted in attenuation of TDF-induced bone loss in mice. LGG probiotics may be a safe and effective strategy to prevent and treat TDF-induced osteoporosis.